Reducing potassium leaching in peat soil using potassium zeolite-based fertilizer (ZEKA) - Eko Noviandi Ginting; Syaiful Anwar; Budi Nugroho; Suroso Rahutomo (Universitas Sebelas Maret, 2025)
Using peat soils for agricultural purposes is challenged by low fertilizer efficiency, especially potassium chloride (KCl). On the other hand, zeolite is a potential material to produce slow-release fertilizers to improve fertilizer efficiency. This study aims to evaluate and compare potassium leaching from a conventional potassium fertilizer, KCl, and a zeolite-based potassium fertilizer, ZEKA, on peat soil columns. The ZEKA fertilizer was produced using two different zeolite particle sizes: coarse zeolite (ZC) and fine zeolite (ZF). The K leached from the fertilizers was measured in a peat soil column. Three zeolite-based potassium fertilizers were formulated: (1) 40% potassium-impregnated zeolite and 60% KCl; (2) 50% potassium-impregnated zeolite and 50% KCl; and (3) 60% potassium-impregnated zeolite and 40% KCl. Since two different sizes of zeolite were used in this study—coarse zeolite (ZC) and fine zeolite (ZF)—the results of the formulation are referred to as follows: ZC-1, ZC-2, ZC-3, ZF-1, ZF-2, and ZF-3. The experiment was completely randomized with eight treatments and three replications. The treatments were as follows: (1) control, (2) KCl, (3) ZC-1, (4) ZC-2, (5) ZC-3, (6) ZF-1, (7) ZF-2, and (8) ZF-3. The findings revealed that ZC-1 and ZF-1 were the most effective ZEKA fertilizer formulations, with total potassium leached of 1.84 grams and 1.05 grams, respectively. Furthermore, the results showed that the total potassium leached from ZEKA fertilizer was 1.71 grams, while the total potassium leached from KCl fertilizer was 2.83 grams. The results showed that ZEKA fertilizer reduced potassium leaching by around 40% compared to KCl fertilizer. Furthermore, the results of this study can be used to improve the efficiency of potassium fertilizer, particularly in agricultural practices on the peatlands.